1992
DOI: 10.1016/s0015-0282(16)54841-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tubal patency by transvaginal sonosalpingography

Abstract: Transvaginal sonosalpingography, with its accuracy and safety, is a promising screening and diagnostic technique in the evaluation of tubal patency on ambulatory basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…19 Oguntoyinbo AE, Amok AOD and Komolafe reported that there is no statistically significant difference (p = 0.237) between the results of the two methods (HSG and SHSG). SHSG is found to be a reliable, relatively inexpensive diagnostic and therapeutic (guided hydrotubation) procedure in the management of female infertility.…”
Section: Discussionmentioning
confidence: 94%
“…19 Oguntoyinbo AE, Amok AOD and Komolafe reported that there is no statistically significant difference (p = 0.237) between the results of the two methods (HSG and SHSG). SHSG is found to be a reliable, relatively inexpensive diagnostic and therapeutic (guided hydrotubation) procedure in the management of female infertility.…”
Section: Discussionmentioning
confidence: 94%
“…Sixty-one Fallopian tubes were examined by both techniques, resulting in concordance of 85%. According to Tufekci et al (1992), the results obtained from transvaginal sonosalpingography and chromolaparoscopy were completely consistent for 76.32% of cases and partially consistent for 21.05% of cases (2). Recently, there have been many studies published using transvaginal sonosalpingography for tubal diagnosis that also reiterate the fact that sonographic diagnosis of patent tubes is reliable.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, the procedure can be performed without prophylactic antibiotics using a regular pediatric Foley's urinary catheter instead of an expensive hysterosalpingography catheter. [1][2][3][4][5] This study is to bring into focus the value of pelvic sonogram in accessing tubal patency in order to overcome the radiation hazard associated with hysterosalpingogram reduce the cost of examination and encourage it at first-line office based procedure for diagnosis of female infertility. 7 Sonosalpingography has been suggested as the first-line method to study tubal patency.…”
Section: Introductionmentioning
confidence: 99%
“…6 This study is to bring in order to study the Department of Obstetrics and Gynaecology, ACPM Medical College, Dhule, Maharashtra, India applicability and accessibility of this method at our institution. 3,4 Sonosalpingography is a simple office procedure which should be used in the preliminary assessment of the uterine cavity and the fallopian tubes. Its use will reduce the need for hysterosalpingography.…”
Section: Introductionmentioning
confidence: 99%